Efeitos da xilanase em dietas contendo DDGS de milho para suínos em crescimento - Souza, Caroline de (2021)
Brazil is the second largest producer of ethanol in the world and its production comes from raw materials such as sugarcane, corn and sorghum. There is a growing demand for corn ethanol, as it is the raw material with the highest production yield for industries. The fluctuation in the prices of ingredients commonly used in swine feed has led the swine industry to seek more economical alternatives for animal feed. From corn ethanol there is the co-product of dry distillery grains (DDGS), an alternative ingredient that can be used in animal feed. One of the main limitations for the use of DDGS in diets refers to its high fiber content, mainly non-starchy polysaccharides (PNAs), which are not degraded by the digestive enzymes of monogastric animals and can compromise the digestibility of nutrients. Another relevant factor regarding the use of DDGS is related to the presence of polyunsaturated fatty acids, which makes intestinal cells more susceptible to oxidation, which may increase oxidative stress and alter immune function. The consumption of foods with PNAs can cause an increase in the rate of passage, increase in viscosity, damage to the intestinal wall, decrease the colonization of microorganisms in the large intestine, impair digestion and absorption of nutrients. Xylanase is an enzyme capable of breaking the beta bonds of PNAs and that can also contribute to the modulation of the intestinal microbiota, reducing undigested substrates, transforming them into oligosaccharides, which can potentiate prebiotic effects. The inclusion of xylanase together with the fibers can stimulate a reduction in pH and an increase in the number of Lactobacillus spp., bringing benefits to the intestinal health of swine. In this way, the use of xylanase in the diet can improve diet digestibility, intestinal modulation and decrease oxidative stress and, thus, favor the use of alternative ingredients and ensure better use of ingredients that have a greater amount of PNAs. Therefore, the aim of the review was to investigate the potential use of DDGS and xylanase on nutrient digestibility, digestible and metabolizable energy values, oxidative stress and intestinal microbiota for growing pigs.